Easy to open? Exploring the 'openability' of hospital food and beverage packaging by older adults. (1st March 2016) - Bell, Alison F.; Walton, Karen L.; Tapsell, Linda C.
Abstract: Food is increasingly a packaged commodity, both in the community and in institutionalised settings such as hospitals, where many older people are malnourished. Previous research with patients aged over 65 years in NSW public hospitals identified difficulties opening milk, water, juices, cereal and tetra packs. The aim of this paper was to assess the ability of well older people living in the community to open food and beverage items routinely used in NSW hospitals in order to gain further insights into the older person/pack interaction and the role of hand and finger strength in pack opening. A sample of 40 older people in good health aged over 65 years from 3 community settings participated in the study. The attempts at pack opening were observed, the time taken to open the pack was measured and the correlation between grip and pinch strengths with opening times was determined. Tetra packs, water bottles, cereal, fruit cups, desserts, biscuits and cheese portions appeared to be the most difficult food products to open. Ten percent of the sample could not open the water bottles and 39% could not open cheese portions. The results were consistent with the previous research involving hospitalised older adults, adding emphasis to the conclusion that food and beverage packaging can be a potential barrier to adequate nutrition when particular types of packaged products are used in hospitals or the community. The ageing population is rapidly becoming a larger and more important group to consider in the provision of goods and services. Designers, manufacturers and providers of food and beverage products need to consider the needs and abilities of these older consumers to ensure good 'openability' and promote adequate nutritional intakes.